The Application of Vertebral Augmentation Procedures and Teriparatide in the Treatment of Osteoporotic Vertebral Compression Fractures [Response to Letter] - Kong M (Dove Medical Press, 2020)
Meng Kong, Chuanli Zhou, Xuexiao Ma Department of Spinal Surgery, Affiliated Hospital of Qingdao University, Qingdao, Shandong Province 266000, People’s Republic of ChinaCorrespondence: Xuexiao MaDepartment of Spinal Surgery, Affiliated Hospital of Qingdao University, No. 59, Hai Er Road, Qingdao, Shandong Province 266000, People’s Republic of ChinaTel + 86 532 18661807895Email ma_xuexiao@126.com With the attempt to explore a reasonable treatment strategy, we presented the positive effectiveness of teriparatide (TPTD) administration in improving quality of life (QOL) and reducing the incidence of new vertebral compression fractures (NVCFs) after percutaneous kyphoplasty (PKP). 1 Being interested with the comment opinion proposed by Zhou et al, we would like to put forward our views.Short-term (eg pain relief, restoration of mechanical stability, mobility improvement and fracture healing) and long-term achievements (eg progressive QOL improvement and prevention of NVCFs) need to be realized in strategies for patients who suffered osteoporotic vertebral compression fractures (OVCFs). 2,3 Vertebral augmentation procedures (VAP), ie percutaneous vertebroplasty (PVP) and/or PKP, is a minimally invasive therapy adopted in the treatment of OVCFs with the aim of prior pain alleviation by stabilizing the vertebral fracture and recovery of function by restoring vertebral body height (VBH). 4 Literature reported that PVP/PKP quickly restored patients’ walking ability soon after operation and improved QOL in the early stage ofOVCFs. 5 On the other hand, except for thewell-known complications induced by surgical procedures, 6 recurrent fractures and the adjacent vertebral fractures are important issues related to VAPs. Logistic regression analysis showed that VAP was a risk factor of vertebra refracture because of increased local vertebral stiffness. 7,8 And this procedure has no contribution to bone healing and the treatment of primary disease, ie osteoporosis. Studies have reported high incidence, up to 21.7%, of new symptomatic compression fractures 1 year after percutaneous vertebroplasty. 9   Read the original article by  Kong et al A letter to the editor has been published for this article